Answer:
![y\text{ = }(-10+5x)/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/d47fvntxysi7uqt2em5d94cn1ft2nkhh9m.png)
Explanations:
The given equation is:
-5x + 2y = -10
Since there are two variables, and there is only one equation, we are going to get our y interms of x.
Let the -5x crosses over the equality sign to the Right Hand Side of the equation. It then becomes + 5x
The equation becomes:
2y = -10 + 5x
Divide both sides of the equation by 2, the equation becomes:
![\begin{gathered} (2y)/(2)=(-10+5x)/(2) \\ y\text{ = }(-10+5x)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1w1gm6w5uy53g3wn2cyjfialqysc7ihs4c.png)